Enhanced Hydrogen Transport over Palladium Ultrathin Films through Surface Nanostructure Engineering. Issue 22 (28th October 2015) - Abate, Salvatore; Giorgianni, Gianfranco; Gentiluomo, Serena; Centi, Gabriele; Perathoner, Siglinda
Abstract: Palladium ultrathin films (around 2 μm) with different surface nanostructures are characterized by TEM, SEM, AFM, and temperature programmed reduction (TPR), and evaluated in terms of H2 permeability and H2 –N2 separation. A change in the characteristics of Pd seeds by controlled oxidation–reduction treatments produces films with the same thickness, but different surface and bulk nanostructure. In particular, the films have finer and more homogeneous Pd grains, which results in lower surface roughness. Although all samples show high permeo‐ selectivity to H2, the samples with finer grains exhibit enhanced permeance and lower activation energy for H2 transport. The analysis of the data suggests that grain boundaries between the Pd grains at the surface favor H2 transfer from surface to subsurface. Thus, the surface nanostructure plays a relevant role in enhancing the transport of H2 over the Pd ultrathin film, which is an important aspect to develop improved membranes that function at low temperatures and toward new integrated process architectures in H2 and syngas production with enhanced sustainability. Abstract : Nano change, big impact : Palladium ultrathin films having different surface nanostructures play a large role in changing the hydrogen‐transfer mechanism. Understanding this process to make tailored surfaces is an important aspect leading to the development of improved membranes for new integrated process architectures with enhanced sustainability.